Lies, Lucas and silence - Grevling, K (Sweet and Maxwell, 2021)
Reflects on the evidential weight of a defendant's lies, and when a jury should receive lies directions (Lucas directions). Examines the requirements for a Lucas direction, when such directions are unnecessary, the role of lies in supporting the prosecution case, and the "innocent" reasons defendants may have for lying. Discusses the relationship between an adverse inferences direction and a lies direction, and the use of hybrid directions.